Prevalence of High Risk HPV in HIV-Infected Women From Belém, Pará, Amazon Region of Brazil: A Cross-Sectional Study - Jacqueline Cortinhas Monteiro; Jacqueline Cortinhas Monteiro; Ricardo Roberto de Souza Fonseca; Ricardo Roberto de Souza Fonseca; Tuane Carolina de Sousa Ferreira; Tuane Carolina de Sousa Ferreira; Luana Lorena Silva Rodrigues; Luana Lorena Silva Rodrigues; Andreza Reis Brasil da Silva; Samara Tatielle Gomes; Rodrigo Vellasco Duarte Silvestre; Andréa Nazaré Monteiro Rangel Silva; et al. (Frontiers Media S.A., 2021)
Human papillomavirus (HPV) is the most common sexually transmitted infection in the world. Several studies have shown a higher prevalence of HPV infection in HIV-infected women. The aim of this study was to determine the prevalence and the genotype diversity of HPV infection in HIV-infected women. From April 2010 to December 2012 cervical specimens were collected from 169 HIV-infected women who screening for cervical cancer at Reference Unit in Belém. The detection of HPV infection was performed by nested PCR and HPV type was performed using a commercial system. The prevalence of HPV infection was 63.3%. Of the 47 genotyped samples, 40.4% was found positive for high risk-HPV 16 and 12.8% for high risk-HPV 52. HPV infection was predominant in the group of women with no incidence of cytological abnormalities and more prevalent in women of reproductive age, unmarried, low education level, and who reported use condoms during sexual intercourse. It was observed an association between HPV infection and independent variables, such as condom use, multiple sexual partners, and history of sexually transmitted diseases. High-risk types of HPV infection were prevalent in our study. Infection with multiple high-risk HPV genotypes may potentiate the development of cervical cancer in HIV-infected women.